PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI LIFESTYLE, CITRA TOKO, DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN ULANG PADA BUTIK HIJAB BILLAH DI SITUBONDO - Qomariah, Isti; Karnadi, Karnadi; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to determine the role of customer satisfaction in mediating lifestyle, store image and digital marketing on repurchase decisions at Hijab Billah store in Situbondo. The population of this research is all Hijab Billah customers. The sampling technique applied in this research is the probability sampling method using random sampling technique. Data analysis and hypothesis test in this research used the Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of the research showed that lifestyle had a positive and significant effect on customer satisfaction, store image had a positive but not significant effect on customer satisfaction, digital marketing had a positive and significant effect on customer satisfaction, lifestyle had a positive and significant effect on repurchase decisions, store image had a positive and significant effect on repurchase decisions, digital marketing had a positive but not significant effect on repurchase decisions, customer satisfaction had a positive and significant effect on repurchase decisions, lifestyle had a positive but not significant effect on repurchase decisions through customer satisfaction, store image had a positive but not significant effect on repurchase decisions through customer satisfaction, and digital marketing had a positive but not significant effect on repurchase decisions through customer satisfaction.